Analysis of determinant factors affecting treatment compliance of hypertensive patients - Iva Fauziani; Anwar Ramli; Julia Fitrianingsih (Jurnal Ilmiah Kesehatan Sandi Husada)
Introduction: Hypertension requires regular and controlled treatment to stabilize blood pressure and prevent complications. Many hypertensive patients do not comply with hypertension treatment procedures, including medication.